MEASURING ENTREPRENEURSHIP DETERMINANTS: EMPIRICAL ANALYSIS - Vinnychuk, Olena; Vodianka, Liubov; Kyfyak, Viktoria; Sybyrka, Liudmyla (Agricultural and Resource Economics: International Scientific E-Journal, 2021)
Purpose. The aim of this article is to assess the main determinants that affect entrepreneurial activity, and also the mechanism of its regulation in five countries (Ukraine, Romania, Lithuania, Poland, Germany) during the period from 2007 to 2018. According to the purpose of the article it was empirically tested a number of hypotheses. Methodology / approach. The canonical correlation method is considered as a basic method for maximum correlations between groups of variables. The group of performance indicators includes: GDP per capita, the volume of output at market prices, Global Competitiveness Index as indicators that most completely reflect the results and efficiency of entrepreneurial activity. The group of factor variables includes entrepreneurial activity determinants, which to some extent affect the change of these entrepreneurial efficiency indicators. The advantages of the proposed method is possibility to analyze the multiple relationships between business results and the determinants that determine it. Results. The article examines a related area of the economy, namely entrepreneurship, which is largely related to agriculture. The article gradually reveals scientific approaches to identifying the determinants of entrepreneurial activity, followed by the methodology of the conducted research, analysis of results and substantiation of hypotheses. According to the aims of the article, the authors have got the following results: 1. To analyze the entrepreneurial environment, a systematic approach must be applied whereby all the determinants of the entrepreneurial environment are interrelated and influence one another. 2. The canonical correlation method allowed to determine the system of entrepreneurial activity determinants and to confirm the statement that each country has its own system of determinants. It is justified by the heterogeneity of the studied data sample, i.e. the presence of a large difference between the numerical values of indicators for selected countries. 3. The human development determinant is the key to business development in the country. Such conclusions are made on the basis of the determinants system analysis in Germany, where indicators of business efficiency are the highest. Originality / scientific novelty. The article proposes a method of assessing the determinants of entrepreneurial activity through the use of the canonical correlation method. This method allows us to investigate the relationship between two sets of variables and is a generalized version of pairwise correlation, as opposed to factor analysis, which is used to establish relationships within one set of variables. Practical value / implications. Presented study aims to extend the empirical knowledge on the measurement of entrepreneurship at the country level and its determinants. In assessing the determinants of the entrepreneurial environment, the main causes that lead to incomplete utilization of entrepreneurial potential remain unaccounted for. Particularly practical meaning may have a thorough analysis of the determinants of entrepreneurial activity in different countries. Modern European integration aspirations of Ukraine should be provided with real socioeconomic transformations in which the development of entrepreneurial activity is key. The beginning of an effective process of forming an efficient strategic approach to creating a favourable entrepreneurial environment for every country is to study the existing experience of other countries. For Ukraine, in particular, this is the experience of the EU countries
Keywords: entrepreneurship determinants, canonical correlation analysis, systematic approach, correlation analysis